2018
DOI: 10.1371/journal.pone.0201452
|View full text |Cite
|
Sign up to set email alerts
|

Zika might not be acting alone: Using an ecological study approach to investigate potential co-acting risk factors for an unusual pattern of microcephaly in Brazil

Abstract: Zika virus infections can cause a range of neurologic disorders including congenital microcephaly. However, while Zika infections have been notified across all regions in Brazil, there has been an unusual number of congenital microcephaly case notifications concentrated in the Northeast of the country. To address this observation, we investigated epidemiological data (2014–2016) on arbovirus co-distribution, environmental and socio-economic factors for each region in Brazil. Data on arbovirus reported cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 66 publications
(83 reference statements)
2
57
1
6
Order By: Relevance
“…Some reasons indicated for this were presented in an ecological analysis study: joint circulation of the virus that causes Chikungunya feber, which exists in this region, could increase the risk of other communicable diseases being transmitted. 122 Another study found higher ZIKA prevalence infection in poorer social classes. 123 The fact that the first notifications of infections occurred in Northeast Brazil, along with the massive media alerts that followed, helped measures to be taken that may possibly have contained greater spread of the virus in other regions.…”
Section: Discussionmentioning
confidence: 97%
“…Some reasons indicated for this were presented in an ecological analysis study: joint circulation of the virus that causes Chikungunya feber, which exists in this region, could increase the risk of other communicable diseases being transmitted. 122 Another study found higher ZIKA prevalence infection in poorer social classes. 123 The fact that the first notifications of infections occurred in Northeast Brazil, along with the massive media alerts that followed, helped measures to be taken that may possibly have contained greater spread of the virus in other regions.…”
Section: Discussionmentioning
confidence: 97%
“…The synergism between cyanobacteria and ZIKV raises awareness that the exposure to STX should also be considered as a public health concern during arbovirus outbreaks. It is important to clarify that microcephaly and other ZIKV-derived congenital abnormalities are multifactorial, therefore, other risk factors may have contributed to foster the uncommon pattern of CZS in Brazil (27). ZIKV outbreaks occurred elsewhere; however, no epidemiological relationship between STX-producing cyanobacteria and congenital malformations derived from ZIKV infection was showed until now.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the total number of cases of ZIKV infection was lower in NE compared to middle-west or southeast (SE) regions (26). Authors have suggested that a co-factor could be acting with ZIKV, contributing to this divergence among NE and other regions of Brazil; however, none has been confirmed until now (27).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, an ecological study at a municipality level across Brazil was unable to correlate the incidence of microcephaly with the incidence of ZIKV infection, but this showed a correlation with poverty index. These data suggested that ZIKV might not be, alone, be responsible for the unusual pattern of microcephaly in Brazil that clustered in the Northeast region (Campos et al 2018).…”
Section: Fig 2 Machine Learning Approach and Genetic Czs/microcephamentioning
confidence: 96%